Efektivitas Assertive Training Untuk Meningkatkan Perilaku Asertif Pada Siswa-Siswi Tahun Ajaran Baru Yang Terdampak Pandemi Covid 19 - Khusnul Khotimah; Sendi Satriadi (Journal on Education, 2024)
Assertive behavior is needed in the learning process at school, it has an impact on the ability of students to develop their self-confidence, so that they are more productive in learning activities. assertive behavior as a behavior that supports equality in human relations, allows individuals to act in their interests, defend themselves without unnecessary anxiety, the ability to express feelings honestly and comfortably, and the ability to exercise personal rights without denying the rights of others. in exercising personal rights without denying the rights of others. The training used in this study is assertive training which is believed to be able to improve the assertive behavior of students. This study aims to determine the level of assertive behavior of students before and after being given assertive training and to determine the effect of assertive training in increasing assertive behavior in students. This research was conducted at SMAN 2 Tambun Utara, Bekasi Regency. The samples in this study were 20 students who were selected by purposive sampling. Based on the calculation results of the non-parametric sign-test statistical test, it is known that the difference in the average value (mean) for the post-test is greater than the pretest, namely 52.05≥46.25. Thus it can be concluded that assertive training can increase assertive behavior in students. This can be seen through the changes that occur in students, such as students becoming more assertive.